BMSC-derived leptin and IGFBP2 promote erlotinib resistance in lung adenocarcinoma cells through IGF-1R activation in hypoxic environment. Issue 1 (2nd January 2020) - Wang, Fan; Zhang, Liyang; Sai, Buqing; Wang, Lujuan; Zhang, Xina; Zheng, Leliang; Tang, Jiuqi; Li, Guiyuan; Xiang, Juanjuan
ABSTRACT: EGFR-TKIs such as erlotinib and gefitinib have been introduced into the first-line treatment for patients having a mutation of deletion in exon 19 or L858R missense mutations in exon 21. Almost all patients who respond to EGFR-TKIs at first place eventually develop acquired resistance after several months of therapy. The secondary mutations and bypass signaling activation are involved in the generation of the resistance. Hypoxia in non-small cell lung cancer (NSCLC) is an important factor in treatment resistance including radiotherapy, chemotherapy and EGFR-TKI therapy. In this study, the effect of hypoxic cancer microenvironment in the bypass signaling activation was investigated. We found that bone marrow-derived mesenchymal stem cells (BMSCs) residing in the hypoxic solid cancer microenvironment highly produced molecules associated with adipocytes including adipokine leptin and IGFBPs. Leptin could induce the resistance of lung cancer cells to erlotinib through activating IGF-1R signaling. IGFBP2 counteracted the activation role of IGF-1 and induced erlotinib resistance by activating IGF-1R signaling in an IGF-1 independent manner. IGFBP2 had synergistic effect with leptin to induce erlotinib resistance. Leptin and IGFBP2 may be predictive factors for acquired resistance for EGFR-TKIs.